AISI 1010 ÇELİK MALZEMENİN SÜRTÜNMELİ DELME YÖNTEMİYLE DELİNMESİNDE DELME KARAKTERİSTİKLERİNİN ARAŞTIRILMASI - DOĞRU, NÜLİFER (Fırat Üniveristesi, 2010)
Sürtünmeli delme ince kesitli profil, boru ve saç malzemelerin delinmesinde kullanılan yeni bir delme yöntemidir. Termal delme ya da sıvayarak delme yöntemi olarak da adlandırılan bu yöntemde dönen konik sivri uçlu bir takımın malzemeye teması sonucu oluşan sürtünme ısısı ile malzemeyi yumuşatıp içine ekstrüze eder ve ince duvarlı bir kovan oluşturarak talaşsız delik açar.Bu çalışmada AISI 1010 çelik kare profiller sürtünmeli delme yöntemi ile CNC freze tezgahında delinmiştir. Çalışmada farklı sürtünme açılarına sahip sinterlenmiş karbür uçlar kullanılmış ve farklı delme parametrelerinde(sürtünme açısı, ilerleme ve delme hızı) deneyler yapılmıştır. Deneyler sonucunda delme parametrelerinin yüzey pürüzlülüğüne, kovan biçimine ve pul biçimine etkileri incelenmiştir. Bu inceleme sonucunda yüzey pürüzlülüğüne, kovan biçimine ve pul biçimine kesme hızı ve ilerlemenin en fazla etkiye sahip olduğu görülmüştür. Kesme hızının artmasıyla kovan yüzey pürüzlülük değerleri azalarak pul ve kovan geometrileri iyileşirken, ilerlemenin artması ile yüzey pürüzlülüğü değerleri artarak pul ve kovan geometrisi bozulmuştur.

Friction drilling is a drilling method used in drilling of thin cross-section profile, pipe and sheet materials. A rotating conical tool with sharpened tip in this method that is also called thermal drilling or flow drilling extrudes the softening work-material by means of the frictional heat caused by its contact to the material, and create a hole with no-chip drilling process by forming a thin-walled bushing.In this study, AISI 1010 steel materials were drilled with CNC milling machine by frictional drilling methods. In the study, sintered carbide tools with different friction angles were used and experiments were conducted under different drilling parameter conditions (friction angle, feedrate and drilling speed). In the results of experiments, the effect of the drilling parameters on surface roughness, bushing shape and form of sealing ring was investigated. According to the results of this study, it was found out that cutting speed and feed rate has the maximum effect on the surface roughness, bushing shape and form of sealing ring on the work-material. Along with the increase of cutting speed , the values of bushing surface roughness decreased; and so, form of sealing ring geometry and bushing geometry improved. On the other hand, along with the increasing feed rate, the values of surface roughness increased; and so, the form of sealing ring geometry and the bushing geometry were distorted.
Investigation of machining characteristics of friction drilling on AISI 1010 steel
Keywords: Makine Mühendisliği